Cases on successful e-learning practices in the developed and developing world methods for the global information economy - Olaniran, Bolanle Abodunrin; Gale Group (Hershey, Penn. Business Science Reference, 2010)
Provides eclectic accounts of case studies in different contexts of e-learning.
Section 1. Innovative uses of e-learning -- Section 2. Addressing various divides in e-learning -- Section 3. User centered focus in e-learning -- Section 4. Special considerations in e-learning and development.
Electronic reproduction.
Keywords: Education -- Computer network resources -- Case studies; Internet in education -- Case studies; Education -- Developing countries -- Computer network resources -- Case studies; Internet in education -- Developing countries -- Case studies; Electronic books